Analyzing and Visualizing Spatiotemporal Patterns of El Niño Teleconnections Using Attribute Trajectories - Long Zhang (Atmosphere, 2021)
El Niño influences the global climate through teleconnections that are not constant in space and time. In order to study and visualize the spatiotemporal patterns of the El Niño teleconnections, a new method inspired by the concept of attribute trajectories is proposed. The coordinates of the trajectories are the normalized anomalies of the relevant meteorological variables in El Niño. The data structures called flocks are extracted from the trajectories to indicate the regions that are subject to the same type of El Niño teleconnection for a certain period. It is then shown how these structures can be used to get a detailed, spatiotemporal picture of the dynamics of the El Niño teleconnections. The comparison between the flocks of the same temporal scale reveals the general dynamics of the teleconnection, while the analysis among the flocks of different temporal scales indicates the relationship between the coverage and their duration. As an illustration of this method, the spatiotemporal patterns of the anomalous temperature increase caused by El Niño are presented and discussed at the monthly and seasonal scales. This study demonstrates the capability of the proposed method in analyzing and visualizing the spatiotemporal patterns of the teleconnections.